Stress testing German banks against a global cost-of-capital shock - Klaus Duellmann; Thomas Kick (Deutsche Bundesbank, 2012)
This paper introduces a stress test of the corporate credit portfolios of 24 large German banks by a two-stage approach: First, a macro-econometric model is used to forecast the impact of a substantial increase of the user cost of business capital for firms worldwide on three particularly export-oriented industry sectors in Germany. Second, the impact of this economic multi-sector stress on banks' credit portfolios is captured by a state-of-theart CreditMetrics-type portfolio model with sector-dependant unobservable risk factors as drivers of the systematic risk. The German credit register provides us with access to highly granular risk information on loan volumes and banks' internal estimates of default probabilities which is key for an accurate assessment of the impact of the stress scenario. We find that the increase of the capital charge for the unexpected loss needs to be considered together with the increase in banks' expected losses in order to assess the change of banks' capital ratios. We also confirm that highly granular information on the level of borrowerspecific probabilities of default has a significant impact on the outcome of the stress test.
Keywords: G21; G33; C13; C15; 330; Asset correlation; portfolio credit risk; macroeconomic stress tests; Kapitalkosten; Schock; Großbank; Kreditrisiko; Kreditwürdigkeit; Bankenkrise; Systemrisiko; Schätzung; Deutschland